Maintaining Momentum in Infant Mental Health Research During COVID-19: Adapting Observational Assessments. (17th March 2021) - Tesson, Stephanie; Swinsburg, Dianne; Kasparian, Nadine A
Abstract: Understanding the potential effects of the COVID-19 pandemic on the developing parent-infant relationship is a priority, especially for medically-fragile infants and their caregivers who face distinct challenges and stressors. Observational assessments can provide important insights into parent-child behaviors and relational risk; however, stay-at-home directives and physical distancing measures associated with COVID-19 have significantly limited opportunities for in-person observational parent-infant assessment. To maintain momentum in our research program during the pandemic, we rapidly pivoted to remote, technology-assisted parent-infant observational assessments. In this commentary, we offer a series of strategies and recommendations to assist researchers in adapting observational parent-infant paradigms. We also discuss the benefits, challenges, and limitations of distance-delivered assessments, and offer considerations for clinical service provision and future research during and post the COVID-19 pandemic.